Prevalence of pre-gestational diabetes among the antenatal women attending a tertiary care center - S. R., Renji; Lekshmi, Sujatha Thankappan; Chellamma, Nirmala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Number of pregnant women with preexisting diabetes is increasing. Hence the detection and management of diabetes from the beginning of pregnancy itself will help to improve the fetal and maternal outcome. Aim of the study was to determine the prevalence of pre-gestational diabetes among the antenatal women attending a tertiary care center and to study the associated factors. Methods: This was a cross sectional study conducted in SAT hospital, Government Medical College, Trivandrum, Kerala, India for one year. HbA1C was the test used to diagnose diabetes. 400 women attending the OP in their first trimester were selected after informed consent. Socio demographic factors assessed by a structured questionnaire. Blood samples were taken for HbA1C. Diagnosis of diabetes was made at levels of HbA1C ≥6.5%. Statistical tests used were mean, standard deviation, chi-square and odds ratio. Results: Prevalence of pre-gestational diabetes was 3.8%.in our study. Main associations were age more than 25 years, body mass index, family history of diabetes, history of intra uterine death, gestational diabetes in previous pregnancy, candidiasis and thyroid disease. Conclusions: Screening of all pregnant women in first trimester itself for diabetes will help in early detection of pre-gestational diabetes, so that anticipation of adverse outcomes and proper management can be done in such cases.